Modulators of histone demethylase JMJD1C selectively target leukemic stem cells. Issue 1 (16th December 2020) - Yang, Yong; Zhang, Xinjing; Zhang, Xiaoyan; Wang, Yishu; Wang, Xintong; Hu, Linda; Zhao, Yao; Wang, Haihua; Wang, Zhanju; Wang, Haiying; Wang, Lin; Dirks, Wilhelm G.; et al.
Abstract : Leukemic stem cells (LSCs) comprise a very rare cell population that results in the development of acute myeloid leukemia. The selective targeting of drivers in LSCs with small molecule inhibitors holds promise for treatment of acute myeloid leukemia. Recently, we reported the identification of inhibitors of the histone lysine demethylase JMJD1C that preferentially kill MLL rearranged acute leukemia cells. Here, we report the identification of jumonji domain modulator #7 (JDM‐7). Surface plasmon resonance analysis showed that JDM‐7 binds to JMJD1C and its family homolog JMJD1B. JDM‐7 did not significantly suppress cell proliferation in liquid cell culture at higher doses, although it led to a significant decrease in semi‐solid colony formation experiments at lower concentrations. Moreover, low doses of JDM‐7 did not suppress the proliferation of erythroid progenitor cells. We identified that JDM‐7 downregulates the LSC self‐renewal gene HOXA9 in leukemia cells. We further found that the structure of JDM‐7 is similar to that of tadalafil, a drug approved by the US Food and Drug Administration. Molecular docking and surface plasmon resonance analysis showed that tadalafil binds to JMJD1C. Moreover, similar to JDM‐7, tadalafil suppressed colony formation of leukemia cells in semi‐solid cell culture at a concentration that did not affect primary umbilical cord blood cells. In summary, we have identified JDM‐7 and tadalafil as potential JMJD1C modulators that selectively inhibit the growth of LSCs. Abstract : JMJD1C is required for the maintenance of both leukemia cells and leukemic stem cells, serving as a potential therapeutic target of acute myeloid leukemia. JDM‐7 (jumonji domain modulator #7) and a structurally similar compound, tadalafil, a drug approved by the US Food and Drug Administration, are able to bind to JMJD1C, resulting in strong attenuation of leukemic stem cells and mild attenuation of leukemia cells, thereby repressing acute myeloid leukemia.